MCM10 is a Prognostic Biomarker and Correlated With Immune Checkpoints in Ovarian Cancer - Wu, Zhenzhen; Wang, Yueyuan; Li, Juan; Wang, Huiling; Tuo, Xunyuan; Zheng, Jing (Frontiers in Genetics, 2022)
Background: Microchromosome maintenance protein 10 (MCM10) is required for DNA replication in all eukaryotes, and it plays a key role in the development of many types of malignancies. However, we currently still do not know the relationship between MCM10 and ovarian cancer (OV) prognosis and immune checkpoints. Methods: The Gene Expression Profiling Interactive Analysis (GEPIA) and Tumor Immunology Estimation Resource (TIMER) databases were used to investigate MCM10 expression in Fan cancer. The Kaplan-Meier Plotter and PrognoScan were used to assess the relationship between MCM10 and OV prognosis. The LinkedOmics database was used to analyze the MCM10 co-expression network and explore GO term annotation and the KEGG pathway. The relationship between MCM10 expression and immune infiltration in OV was investigated using the TIMER database. cBioPortal database was used to explore the relationship between MCM10 expression and 25 immune checkpoints. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) was performed to detect MCM10 expression. The prognosis was also analyzed by distinguishing between high and low expression groups based on median expression values. Results: The results of the three data sets (220651_s_at, 222962_s_at and 223570_at) in KM Plotter all indicated that the overall survival(OS) of the high MCM10 expression group was lower than that of the low expression group OV, and the results of GSE9891 also reached the same conclusion. The expression level of MCM10 was negatively correlated with B cells and CD8+T cells, and positively correlated with CD4+T Cells and Macrophages. GO term annotation and KEGG pathway analysis showed that the co-expressed genes of MCM10 were mainly enriched in cell cycle and DNA replication. The alterations in MCM10 coexisted statistically with the immune checkpoints CTLA4, TNFSF4, TNFSF18, CD80, ICOSLG, LILRB1 and CD200. PCR results displayed that MCM10 was highly expressed in OV tissues, and the increased expression of MCM10 was significantly associated with poor overall survival. Conclusion: These results demonstrated that high expression of MCM10 was associated with poor prognosis in OV and correlated with immune checkpoints.